Nutritional, sanitary, reproductive and environmental management of 26 dog breeding kennels (Canis lupus) in the Great Metropolitan Area in Costa Rica (UNED Research Journal, 2019)
Introduction: Dog breeding kennels are establishments dedicated to the reproduction, breeding and trade of one or more breeds, either occasionally or permanently. Objective: We intend to analyze the activities that take place in registered kennels to understand how breeding kennels work in the Great Metropolitan Area (GAM, for its acronym in Spanish) in Costa Rica. Methods: In 2017 and 2018 we contacted the National Service of Animal Health (SENASA, for its acronym in Spanish) and three private associations related to breeding and trade activities in the country. Using survey tools, we collected the information related to animal management, feeding, hygiene, reproduction, health, facilities, and waste disposal. Results: We identified a total of 111 dog breeding production systems in the national territory, according to the lists of four entities, from which only 26,13% are registered in the regulating entity, SENASA. From the 26 kennels visited in the GAM, 23 different dog breeds are bred and managed, and the sale prices for these animals fluctuate between $500 and $3 500. In the case of nutrition management, we identified balanced diets and the additional use of nutritional supplements to improve nutrient intake, but these could cause an excess of the nutritional requirements. As for reproduction, ultrasounds and progesterone tests are used to determine the best moment for the mounting. To manage waste and cleanliness, the management is similar between systems, where producers take charge or receive the support of an external party. Conclusions: Every dog breeding kennel system in the Great Metropolitan Area in Costa Rica has its own management strategies, which depend on the experience and technical support processes received by those in charge of the process.
Keywords: breeding; reproduction; feeding; facilities; animal handle